HASIL UJI IMPLEMENTASI PNPM MANDIRI PERDESAAN KABUPATEN BANYUMAS - Indiahono, Dwiyanto (Jurnal Kawistara, 2014)
Previous research have shown that the performance of the implementation of the National Programof Rural Self Empowerment (PNPM-Mandiri Perdesan) in Banyumas is determined by variables: thecapacity of the target group, the capacity of the implementing agencies, the quality of communicationand socialization, as well as monitoring (monitoring) as an intermediate variable. Quantitative researchinvolving 400 respondents spread 5 districts and 20 villages were selected at random has been done.Data were processed and analyzed include correlation, regression testing, and test the model. Theresults of this study indicate that the implementation of PNPM-Mandiri Rural models tested can beused to examine the implementation of PNPM Mandiri Rural elsewhere and can be used to check forother poverty reduction programs based on empowerment.